Simulation of the ethylene oxide production process in ChemCAD® simulator - Pérez Sánchez, Amaury (2021)
Fil: Pérez Sánchez, Amaury. Universidad de Camagüey “Ignacio Agramonte Loynaz Facultad de Ciencias Aplicadas; Cuba.